Cell interactions in the immune response in vitro. II. The requirement for macrophages in lymphoid cell collaboration. - Feldmann, M (1972)
The requirement for macrophages in thymus-dependent antibody responses was studied in vitro. Three different macrophage-deficient cell populations were studied: spleen cells passed through a glass bead column at 37 degrees C, spleen cells cultured with specific antimacrophage serum, and thoracic duct lymphocytes. These cell populations from mice primed to dinitrophenylated (DNP) fowl gamma globulin were unable to respond to the homologous conjugate in vitro. DNP-reactive B cells were present in normal proportions, since all three macrophage-depleted populations responded normally to macrophage-independent and thymus-independent DNP flagella. Carrier-reactive T cells were present, as the helper capacity of carrier-primed spleen cells was the same as carrier-primed lymphocytes, and thoracic duct lymphocytes are a well-established source of helper cells. The inhibition of the cooperative response was thus due to removal of macrophages, and this was proven by restoration of thymus-dependent anti-DNP responses by small numbers of anti-theta-treated peritoneal exudate cells. These results suggest that macrophages are essential in cell collaboration, While their exact function in cell collaboration is not yet known, the above observation suggests that the mechanism of T-B collaboration involves the surface of macrophages.